METODE EKSPERIMEN DAN METODE DEMONSTRASI TERHADAP PENINGKATAN HASIL BELAJAR IPA - Istiqomah, Istiqomah; Supriyatno, Arie; Mahardika, Astuti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2014)
The purpose of this study was to determine differences in the effect of the experimental method and the method to learn science demonstrations against the results of class V SD Negeri Bojong 1 Mungkid. This research uses experimental research of pure (True Experimental Design). Experimental research design used was pretest-posttest control group design. The population of this study were all students of class VA and VB SD Negeri Bojong 1 Mungkid. The sampling technique used was purposive sampling technique consisted of 22 students who received treatment in the form of learning using the experimental method and the 22 students who received treatment in the form of learning by using the method of demonstration. Methods of data collection was performed using the test results and the observation sheet psychomotor learning. Differences influence experimental methods and methods demonstration on learning outcomes IPA calculated using analysis of variance with SPSS 16.0 forWindows. Based on the test, a score Fhitung 4.509> Ftable 4,073dan sig 0.040 <0.05. It concluded that Ho is rejected and Ha accepted which means that there is a significant difference between the value posttest experimental class I (experimental method) and the posttest experimental class II (methods of demonstration) and greater influence is the experimental method. Thus the experimental method is better than demonstration method in teaching science.